2004
DOI: 10.1039/b411306n
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Hula-twist photoisomerization of cinnamate esters in organic glass

Abstract: Irradiation of ethyl cis-o-fluorocinnamate and related compounds in organic glass led to two HT-isomerization processes that exhibit a strong preference at C-beta than at C-alpha as shown by low temperature UV absorption spectroscopy and supported by ab initio calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…In summary, based on the results reported above, we conclude that naphthylphenylethylenes undergo regioselective HT photoisomerization at the benzylic site when irradiated in low temperature glasses. This conclusion is in agreement with other reported examples of HT photoisomerization, in particular the regioselective HT isomerization of diphenylbutadienes (13) and cinnamates (21) and computational results (22,23). It questions the conclusion of “No HT” of cis ‐ 1 (14) and whether it is appropriate to apply the Occam razor principle in determining reaction mechanisms of concern (8).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In summary, based on the results reported above, we conclude that naphthylphenylethylenes undergo regioselective HT photoisomerization at the benzylic site when irradiated in low temperature glasses. This conclusion is in agreement with other reported examples of HT photoisomerization, in particular the regioselective HT isomerization of diphenylbutadienes (13) and cinnamates (21) and computational results (22,23). It questions the conclusion of “No HT” of cis ‐ 1 (14) and whether it is appropriate to apply the Occam razor principle in determining reaction mechanisms of concern (8).…”
Section: Resultssupporting
confidence: 93%
“…The combined results of cis-1 and cis-2 revealed a high regioselectivity for HT photoisomerization favoring the benzylic site. Similar selectivity was, in fact, detected in low temperature photoisomerization of isomers of DPB (13) and a cinnamate ester (21).…”
Section: Resultssupporting
confidence: 65%
“…The isomerization degree increased to 0.011 with an increase in the irradiation time up to 100 min. These results suggested that the E – Z isomerization occurred in the solid state, whereas the solid circumstance restricted the isomerization accompanied by a free volume change according to the literature 8. The E – Z isomerization may be attributed to the mobility of the P3HCA chains at room temperature as seen in the local rotation of phenylester polymers 9.…”
Section: Resultssupporting
confidence: 60%
“…These results suggested that the E-Z isomerization occurred in the solid state, whereas the solid circumstance restricted the isomerization accompanied by a free volume change according to the literature. 8 The E-Z isomerization may be attributed to the mobility of the P3HCA chains at room temperature as seen in the local rotation of phenylester polymers. 9 Although the ratio of E-Z isomerization was very small, it is sufficient to make a change of stable polymer chain conformation from extended to bended one.…”
Section: Photoreactionmentioning
confidence: 99%
“…The result showed that fluorescence spectra of t-1 and t-4 were identical to those of c-1 and c-4, respectively, suggesting that the cis-trans photoisomerization could occur even in organic glass. 15 Emission of c-2 displays a blue shift compared to that of t-2 at 78 K. However, when the temperature was raised to 297 K, the emission from these two isomers became identical. This probably indicates photoisomerization at room temperature (see ESI, Fig.…”
Section: Temperature Dependencementioning
confidence: 93%